Telaprevir-based therapy for treatment of HIV-1 and hepatitis C virus co-infected patients: An early access programme. Issue 6 (December 2015) - Gori, Andrea; Doroana, Manuela; Chernova, Oksana; Rockstroh, Jürgen K.; Banhegyi, Denes; Bergin, Colm; Verucchi, Gabriella; Liu, Chris; DeMasi, Ralph; Hadacek, Blanca; Nelson, Mark
Summary: Objectives: HPC3005 is a multicentre, open-label, telaprevir trial in HCV/HIV coinfected patients with severe fibrosis or compensated cirrhosis. Methods: Patients were treated with telaprevir 750 mg every 8 h (1125 mg if on efavirenz) plus pegylated interferon-alpha (PEG-IFN, 180 μg once-weekly) and ribavirin (RBV, 800 mg/day) for 12 weeks, followed by 36 weeks of PEG-IFN/RBV. Results: Mean age was 44 years, 97/118 patients were male and all were Caucasian, 68 had severe fibrosis and 50 had cirrhosis. Seventy-eight had HCV RNA levels ≥800 000 IU/mL, 72 had HCV genotype 1a, baseline HIV RNA was <50 copies/mL in 112 patients. Overall, 114/118 patients continued antiretroviral treatment, 4 were untreated. Seventy-five patients received tenofovir and 74 emtricitabine; in addition 53 received atazanavir/ritonavir, 43 raltegravir, and 24 efavirenz. By intention-to-treat, 78 (66%) patients achieved SVR24. Nineteen discontinued telaprevir, 8 for virological endpoint, 5 for adverse events (2 anaemia, 2 rash, 1 asthenia), 5 for non-compliance and 1 withdrew consent. The most common adverse events were anaemia (36 patients), thrombocytopaenia (33), rash (26), bilirubin increase (17), and neutropenia (16). Conclusions: In this early access programme in coinfected patients with severe fibrosis or cirrhosis, 66% of patients achieved SVR. The most common adverse events were haematological. Clinical Trial Number:NCT01500616 . Highlights: We studied telaprevir in HCV/HIV coinfected individuals with severe advanced liver disease. Sixty-six percent of patients achieved SVR. The most common adverse events were of haematological nature. Discontinuation for adverse events was uncommon.